As estratégias discursivas e mercadológicas da Folha de S. Paulo na captação do público leitor - Müller, Fabrise de Oliveira (2016)
Media coverage brings up a new attitude from readers concerning journalistic production. The newspaper is conditioned to proposing new communication contracts with ways to prospect readers in order to keep in touch with an increasingly competitive market. Prospecting strategies aim to entice and persuade the partner in communicative exchange, causing them to share intentionality. The newspaper does this through texts that appeal to the controversy, drama, comparisons, metaphors, capturing the reader through emotion. At the same time, marketing decisions considering the profitability of the vehicle are highlighted: the more they get readers, the more they achieve financial results. The newspaper is a product and the reader receives customer or client status. Considering the proposals, the following research aims to analyze the communication contracts established by the Folha de S. Paulo in media environment to prospect readers. Theoretical discussions are based on the theoretical contributions of Maingueneau (2013; 2015), Verón (2004) and Charaudeau’s (2010; 2013) semiolinguistics analysis. After analyzing the printed newspaper covers of Folha de S. Paulo, in-depth interviews were conducted with the newsroom, marketing, and commercial sector professionals. The results indicate that communication contracts are signed by a brand valuation and newspaper content, attempting to interact with the reader through events, the constitution of covers with shocking images which can raise emotions, appreciation of columnists and reporters, as well as a constant search for exclusive news.